Financial Report Analysis to Assess Financial Performance at PT. Astra International Tbk for the 2019 – 2022 Period - Sitorus, Fungky Yohanes; Br Purba, Rahima (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study,